Carboxyl-modified colloidal crystal templates for the synthesis of three-dimensionally ordered macroporous SMMN2O5 mullite and its application in NOx-assisted soot combustion. Issue 22 (30th October 2018) - Chen, Yongjie; Du, Chun; Lang, Yun; Jia, Liwei; Chen, Rong; Shan, Bin
Abstract : Schematic illustration of NO x -assisted soot combustion. Abstract : The strict regulation of emission levels demands the development of novel catalysts and techniques to remove soot from exhaust gas. Three-dimensionally ordered macroporous SmMn2 O5 (3DOM SMO) mullite catalysts with large pore sizes and interconnected macroporous frameworks were designed and synthesized successfully by applying carboxyl-modified colloidal crystal templates, and tested for soot combustion reaction. The catalytic performance for soot combustion was evaluated using temperature-programmed oxidation (TPO) reaction technology under "loose" contact conditions. Meanwhile, the physical and chemical properties were characterized by means of XRD, SEM, BET, XPS, O2 -TPD and H2 -TPR. The thermostability of the polymer templates was investigated by TG measurements. The TG results and SEM images showed that the template with CPMMA-5% exhibited the desirable decomposition temperature and hexagonal close-packed structure. The 3DOM SMO prepared with CPMMA-5% as the template exhibited the overall highest catalytic activity for soot combustion. The corresponding T 50 was 366 °C and the CO2 selectivity was 99.5%. The O2 -TPD and H2 -TPR measurements indicated higher mobility and better reducibility of surface adsorbed oxygen on the 3DOM SMO sample than on other specimens, leading to its enhanced catalytic performance.